Dimensions of learning orientation and its impact on organizational performance and competitiveness in SMEs - Vega Martinez, Javier Eduardo; Martinez Serna, María del Carmen; Parga Montoya, Neftalí (Journal of Business Economics and Management, 2020)
There is evidence that indicate a positive relationship of learning orientation (LO) with organizational performance in SMEs of emerging economies. However, there are only few studies that investigate how each one of the dimensions of learning orientation (LO) contributes to variables of results such as competitiveness and organizational performance. The purpose of this study is to analyze the direct effects of each dimension of the construct (LO) with organizational performance and competitiveness, from a quantitative cross-sectional study implemented in 400 SMEs of Aguascalientes city, Mexico using SEM technique. The findings reveal that there is a direct and significant relationship between commitment to learning and shared vision with competitiveness; open-mindedness turned out to have a non-significant positive relationship with competitiveness. While the relationship of open-mindedness and commitment to learning have a positive and significant influence on organizational performance, not so shared vision that has a negative and significant influence on organizational performance. The originality of this paper, is that there is limited contributions of the relationship of LO with each dimension of competitiveness, and performance in SMEs worldwide. Among the implications found it is that the existing evidence may result different in other economies and large businesses.